Estructura organizacional y desempeño profesional en la escuela isidro ayora de la ciudad de Latacunga. Diseño de un manual de funciones para docentes y directivos. - Jiménez Morales, Jorge Guillermo (2017)
The educational organization is a subject of permanent debate, where a traditional administration maintains, with autocratic directors who do not ensure the full participation of the main pedagogical actors and others. The constant change of authorities with little knowledge in administration education that affects the motivation, performance and professional success of the human talent of the "Isidro Ayora" school in Latacunga city. For this reason, the present investigative work designs a Manual of Functions, that becomes a dynamic management tool that determines the identification and nature, the position, the description of essential functions framed within the current laws and the Code of Conduct. Coexistence; the identification of behavioral competencies such as leadership and assertive communication and the requirements of academic training and experience that a quality manager must have. The organizational structure is fundamental in an institution to achieve its objectives and foster confidence and security in its members. Considering that, the administrative process is not linear, but it is integrated and integrating. A qualitative research was carried out using the technique of the focal groups to analyze the current situation and delineate the contents of the manual of functions in workshops held with the directors, members of the Executive Council, of the School Government, the coordinating teachers of each grade and secretariat. The democratic participation of all the educational actors will guarantee the functionality of the manual and will improve the processes of planning and organization, concluding that power and authority constitute means of influence but that the communication, the motivation, the leadership and the taking of opportune decisions and with knowledge of cause determine the efficiency and effectiveness.